A yaw attitude determination method based on coarse sun sensor information for the GEO satellite. Issue 1 (1st December 2022) - Yin, Jing; Liu, Jiang; Yang, Fan
Abstract: The coarse sun sensor is used to measure the satellite's attitude relative to the sun. If the satellite can maintain the earth-pointing attitude by the high-precision sensor, the coarse sun sensor information can be used to determine the satellite's yaw attitude, which is effective in coping with the short-term failure of the satellite's yaw attitude sensor. This paper proposes a method to determine the yaw attitude of the satellite using the coarse sun sensor information. In view of the main factors affecting the accuracy of the coarse sun sensor, the measures to improve the yaw accuracy are proposed: the sensor calibration method based on historical data and effective measurement range selection. Simulation with satellite onboard data, the expected function can be achieved, and by correcting the measurement data, the yaw attitude accuracy can be significantly improved.